DRAMA-BASED IMMERSIVE LEARNING IN ISLAMIC BOARDING SCHOOLS: A NOVEL APPROACH TO ARABIC LANGUAGE ACQUISITION - Subakir, Fairuz; Siti Nikmatul Rochma; Nur Fera Khalifah; Nuraeni Rahmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study investigates the implementation of drama-based immersive learning as an innovative approach to Arabic language acquisition in an Islamic boarding school context. Employing a qualitative case study design, the research explores how the “Gebyar Seni Darussalam (Pra Drama Arena)” program facilitates students’ communicative competence through performance-based activities. Data were collected through observations, interviews, and document analysis involving Grade 3 intensive and Grade 4 students. The findings reveal that drama-based immersive learning significantly enhances students’ Arabic speaking proficiency, integrates four language skills, increases learner engagement, and strengthens confidence and willingness to communicate. More importantly, the study demonstrates that language acquisition occurs most effectively within an immersive environment where learners actively use language in meaningful social interactions. The study proposes a novel conceptual model, Institutionalized Drama-Based Immersive Learning (IDIL), which integrates performative pedagogy, continuous language exposure, and institutional support into a holistic learning ecosystem. This model offers both theoretical and practical contributions to Arabic language education by shifting the focus from instruction to experience and from classroom practice to institutionalized immersion. The findings suggest that drama-based immersion can serve as a scalable and sustainable model for enhancing language proficiency in similar educational settings.